Klemens Aleksandryjski, Wypowiedzi profetyczne - Pawłowski, Wojciech (Vox Patrum, 2025)
The work contains an introduction and a translation into Polish of the work "Eclogae propheticae" ("Selections from the prophetic scriptures") of Clement of Alexandria.